Post-Induction Management in Patients With Left-Sided RAS and BRAF Wild-Type Metastatic Colorectal Cancer Treated With First-Line Anti-EGFR-Based Doublet Regimens: A Multicentre Study - Parisi, Alessandro; Cortellini, Alessio; Venditti, Olga; Filippi, Roberto; Salvatore, Lisa; Tortora, Giampaolo; Ghidini, Michele; Nigro, Olga; Gelsomino, Fabio; Zurlo, Ina Valeria; Fulgenzi, Claudia; Lombardi, Pasquale; et al. (Frontiers in Oncology, 2021)
Background Few data regarding post-induction management following first-line anti-epidermal growth factor receptor (EGFR)-based doublet regimens in patients with left-sided RAS/BRAF wild-type metastatic colorectal cancer (mCRC) are available. Methods This multicenter, retrospective study aimed at evaluating clinicians’ attitude, and the safety and effectiveness of post-induction strategies in consecutive patients affected by left-sided RAS/BRAF wild-type mCRC treated with doublet chemotherapy plus anti-EGFR as first-line regimen, who did not experience disease progression within 6 months from induction initiation, at 21 Italian and 1 Spanish Institutions. The measured clinical outcomes were: progression-free survival (PFS), overall survival (OS), adverse events, and objective response rate (ORR). Results At the data cutoff, among 686 consecutive patients with left-sided RAS/BRAF wild-type mCRC treated with doublet plus anti-EGFR as first-line regimen from March 2012 to October 2020, 355 eligible patients have been included in the present analysis. Among these, 118 (33.2%), 66 (18.6%), and 11 (3.1%) received a maintenance with 5-fluorouracil/leucovorin (5FU/LV)+anti-EGFR, anti-EGFR, and 5FU/LV, respectively, while 160 (45.1%) patients continued induction treatment (non-maintenance) until disease progression, unacceptable toxicity, patient decision, or completion of planned treatment. The median period of follow-up for the overall population was 33.7 months (95%CI = 28.9–35.6). The median PFS values of the 5FU/LV+anti-EGFR, anti-EGFR, 5FU/LV, and non-maintenance cohorts were 16.0 (95%CI = 14.3–17.7, 86 events), 13.0 (95%CI = 11.4–14.5, 56 events), 14.0 (95%CI = 8.1–20.0, 8 events), and 10.1 months (95%CI = 9.0–11.2, 136 events), respectively (p < 0.001). The median OS values were 39.6 (95%CI = 31.5–47.7, 43 events), 36.1 (95%CI = 31.6–40.7, 36 events), 39.5 (95%CI = 28.2–50.8, 4 events), and 25.1 months (95%CI = 22.6–27.6, 99 events), respectively (p < 0.001). After adjusting for key covariates, a statistically significant improvement in PFS in favor of 5FU/LV+anti-EGFR (HR = 0.59, 95%CI = 0.44–0.77, p < 0.001) and anti-EGFR (HR = 0.71, 95%CI = 0.51–0.98, p = 0.039) compared to the non-maintenance cohort was found. Compared to the non-maintenance cohort, OS was improved by 5FU/LV+anti-EGFR (HR = 0.55, 95%CI = 0.38–0.81, p = 0.002) and, with marginal significance, by anti-EGFR (HR = 0.67, 95%CI = 0.51–0.98, p = 0.051). No difference was found in ORR. Any grade non-hematological and hematological events were generally higher in the non-maintenance compared to the maintenance cohorts. Conclusion Among the treatment strategies following an anti-EGFR-based doublet first-line induction regimen in patients affected by left-sided RAS/BRAF wild-type mCRC treated in a “real-life” setting, 5FU/LV+anti-EGFR resulted the most adopted, effective, and relatively safe regimen.